Penegakan Hukum terhadap Tindak Pidana Kekerasan Berbasis Gender Online (KBGO) Lintas Wilayah oleh Kepolisian Daerah Kalimantan Tengah - Pirna pirna; Indang Sulastri; Istani; Aris Toteles (Jurnal Hukum Lex Generalis, 2026)
This study aims to analyze law enforcement against cross-regional Online GenderBased Violence (KBGO) offenses by the Central Kalimantan Regional Police and the obstacles encountered. The study uses an empirical juridical method with a descriptive-analytical approach based on primary and secondary data. The results show that law enforcement has been carried out in accordance with the provisions of the TPKS Law, the ITE Law, and the National Police Regulation on Criminal Investigation. The problem does not lie in the regulatory aspect, but in tracking anonymous perpetrators, digital evidence, and cross-regional coordination. Therefore, it is necessary to improve investigator capacity and strengthen interregional cooperation.